(untitled) (Journal of Contemporary Studies, 2021)
Russia has carefully employed its military and diplomatic tools of statecraft in the Syrian conflict. The Syrian war has been a quagmire with the diversity of actors involved having national, regional, and global interests. Russia’s decisive role and direct involvement in the conflict has brought it to the forefront of Middle Eastern politics. Russia after taking control of the Syrian airbase can carry out missions across the Levant and Eastern Mediterranean. Moreover, Russia has not only courted the regional states into its side particularly Turkey but has also successfully averted any direct clash with the US and Israel in Syria. Russia has been able to demonstrate its strategic will to take decisive actions and transforming the risks into opportunities. Syria has brought the Russians back to the international decision-making as an important player. Moreover; Syria has provided Russia with a geopolitical advantage in the Middle East and to uphold Russian status as a global power.